2023
DOI: 10.1038/s41598-023-30068-2
|View full text |Cite
|
Sign up to set email alerts
|

FUS regulates a subset of snoRNA expression and modulates the level of rRNA modifications

Abstract: FUS is a multifunctional protein involved in many aspects of RNA metabolism, including transcription, splicing, translation, miRNA processing, and replication-dependent histone gene expression. In this work, we show that FUS depletion results in the differential expression of numerous small nucleolar RNAs (snoRNAs) that guide 2’-O methylation (2’-O-Me) and pseudouridylation of specific positions in ribosomal RNAs (rRNAs) and small nuclear RNAs (snRNAs). Using RiboMeth-seq and HydraPsiSeq for the profiling of 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 69 publications
(121 reference statements)
0
5
0
Order By: Relevance
“…33 FUS is a multifunctional protein involved in almost all aspects of mRNA metabolism including mRNA stability, transcription, splicing, miRNA processing, and translation. 34,35 Indeed, FUS is largely a nuclear protein implicated in transcription and posttranscriptional maturation/processing of pre-mRNAs, it is necessary to investigate the regulation of FUS on ALDH2 transcription. First, we performed chromatin immunoprecipitation-PCR assays using antibodies that recognize FUS or RNAP II to evaluate their binding event on the ALDH2 gene promoter.…”
Section: Discussionmentioning
confidence: 99%
“…33 FUS is a multifunctional protein involved in almost all aspects of mRNA metabolism including mRNA stability, transcription, splicing, miRNA processing, and translation. 34,35 Indeed, FUS is largely a nuclear protein implicated in transcription and posttranscriptional maturation/processing of pre-mRNAs, it is necessary to investigate the regulation of FUS on ALDH2 transcription. First, we performed chromatin immunoprecipitation-PCR assays using antibodies that recognize FUS or RNAP II to evaluate their binding event on the ALDH2 gene promoter.…”
Section: Discussionmentioning
confidence: 99%
“…Fused in Sarcoma (FUS) is an RNA/DNA-binding protein present in both the nucleus and cytoplasm with significant roles in binding, splicing and transporting RNAs [ 217 ]. It was recently shown that FUS interacts with snoRNAs and that loss of FUS expression can result in increased snoRNA expression and alter both pseudouridylation and 2’-O-methylation levels in rRNA and spliceosomal small nuclear RNAs [ 218 ]. Crosslinking immunoprecipitation followed by sequencing (CLIP-seq) and RNA immunoprecipitation (RIP) experiments showed that FUS interacts with snoRNAs at sites that overlap the snoRNAs’ host genes.…”
Section: Snorna Associated Factorsmentioning
confidence: 99%
“…However, previous studies suggest that FUS binds introns of genes [ 219 ]. Furthermore, knockout experiments in cell lines suggest that FUS binds snoRNAs prior to snoRNP assembly, as there is no change in core protein expression levels upon knockout of FUS [ 218 ]. Loss of FUS expression leads to defects in splicing, which may be related to the role FUS plays in modulating spliceosomal RNA modification [ 219 ].…”
Section: Snorna Associated Factorsmentioning
confidence: 99%
“…In neuropsychiatric disorders, SNORD114‐26 was downregulated in individuals with major depressive disorder (MDD), and similar expression was noted for SNORD114‐10 in the hippocampus of suicide victims (Glavan et al, 2021; Mahajan et al, 2018). The expression pattern of the snoRNAs from this cluster varies widely in neurodegenerative disorders such as Alzheimer's disease (AD) and amyotrophic lateral sclerosis (ALS) (Fitz et al, 2021; Gawade et al, 2023).…”
Section: Role Of Dlk1‐dio3 C/d Box Snornas In Developmental Disordersmentioning
confidence: 99%